Upaya Pencegahan Penyakit Ikan di Desa Silirejo, Kecamatan Tirto Kabupaten Pekalongan - Linayati, Linayati; Mardiana, Tri Yusufi; Syakirin, Muhammad Bahrus; Madusari, Benny Diah; Purnama, Candra Adi (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
This Community Service activity was held in the village of Silirejo, Tirto District, Pekalongan Regency. The purpose of this activity is to increase public knowledge about efforts to prevent fish diseases in fish farming by the general public. There were 25 participants consisting of PKK women from the surrounding area. The material presented includes symptoms of sick fish, causes, treatment and prevention. The activity is carried out in 3 methods, namely presentation with slides, discussion and the last is an assessment through questions that will be answered by the participants. The results of this activity showed an increase in knowledge based on the number of correct answers. There was an increase from 20% to 80% of participants who answered correctly at the end of the activity.